Perceived achievement of subject learning outcomes, pedagogical strategy, facilitating skills and academic performance of university engineering students. - Wai-chi Chu, Rodney; Ying-yin Wong, Alex; Ming-yin Chan; Shek, Daniel T. L. (International Journal of Child & Adolescent Health, 2020)
Based on students' responses, this study examined the inter-relationships amongst perceived achievement of learning outcomes, teacher's pedagogical strategy as well as facilitating skills, and professional knowledge of the students. Pre-test and post-test data on the achievement of learning outcomes (N = 36) and data based on additional questions in the post questionnaire addressing pedagogical strategies and facilitating skills of the teachers were collected. Results showed that after flipped classroom learning, posttest scores on the subject intended learning outcomes were higher than the pretest scores. Pearson correlation analyses also showed that perceived achievement of the intended learning outcomes of the subject and teachers' pedagogical knowledge/strategies as well as facilitating skills were positively correlated with academic performance of students.